Genetic variation and phylogeography of free-living mouse species (genus Mus) in the Balkans and the Middle East - Macholán, M; Vyskocilová, M; Bonhomme, F; Krystufek, B; Orth, A; Vohralík, V (Molecular ecology, 2007)
This work presents a study of the distribution and pattern of variation throughout the ranges of three free-living mouse species of the genus Mus-M. macedonicus, M. spicilegus, and a M. cypriacus - based on sequencing of two segments of the mitochondrial DNA (mtDNA) control region. The study shows a similar level of variability in the three species and suggests their recent population expansion. The highest proportion of variation is found within populations indicating low genetic structuring. Phylogenetic analysis confirms the significant divergence of a mitochondrial lineage of M. macedonicus from Israel, recently described as a new subspecies, M. macedonicus spretoides. Conversely, no genetic hiatus is revealed between European and Asian populations of M. macedonicus macedonicus. Although phylogenetic relationships among M. spicilegus populations could not be unravelled precisely, the results suggest a recent westward expansion of the species. The mtDNA divergence between M. macedonicus and M. spicilegus is 7.3%, suggesting their split between c. 700,000 and 1 million years ago. These dates correspond with a coalescent estimate about 720,000 years ago. On the other hand, M. cypriacus appeared almost twice as divergent from the former species (4.5%) as from the latter (8.8%) suggesting a divergence of c. 430,000-610,000 years ago (coalescent approximately 490,000 years ago) and 830,000-1.2 million years ago (coalescent approximately 780,000 years ago), respectively. Approximate times of population expansion have also been estimated for all taxa and groups of populations. Existence of several glacial refuges and various colonization scenarios are discussed; since all estimated divergence times fall within interglacial periods it seems that climatic oscillations did not play a crucial role in the evolution of the three species.
Keywords: myši; fylogeneze; Europe; mitochondriální DNA; Molecular Sequence Data; Haplotypes; Geography; Genetic Variation; Evropa; Base Sequence; Střední východ; Middle East; Mice; haplotypy; Animals; DNA, Mitochondrial; Sequence Analysis, DNA; zvířata; genetická variace; sekvence nukleotidů; Phylogeny; sekvenční analýza DNA; populační dynamika; Population Dynamics; zeměpis; molekulární sekvence - údaje